Manchester Asthma and Allergy Study: Low-allergen environment can be achieved and maintained during pregnancy and in early life - Custovic,A; Simpson,BM; Simpson,A; Hallam,C; Craven,M; Brutsche,M; Woodcock,A (Journal of Allergy and Clinical Immunology, 2000)
Background: Early exposure to dust mite allergens may be critical for primary sensitization. Reducing exposure may offer a realistic chance for primary prevention of sensitization and asthma, but it is essential to implement measures that can achieve and maintain the low-allergen environment. Objective: Our purpose was to assess the effectiveness of mite allergen avoidance measures in achieving and maintaining a low-allergen environment during pregnancy and in the first year of life. Methods: The Manchester Asthma and Allergy Study is a prospective, prenatally randomized study that follows the development of asthma and atopy in a cohort of infants at high risk (both parents atopic) who are randomly allocated to full mite allergen avoidance or to a normal regimen. Avoidance measures comprise (1) mite-proof covers (mattress, pillow, and quilt) for parental bed, (2) high-filtration vacuum cleaner, (3) vinyl flooring in infant's bedroom, (4) new crib and portable crib mattresses encased in mite-proof material, (5) benzyl benzoate (Acarosan) applied on carpets and soft furniture, (6) bed linens washed in hot water weekly, and (7) washable soft toys. Dust samples from the parental bed, bedroom floor, living room floor, infant's mattress, and nursery floor were collected between the 10th and 14th weeks of pregnancy, immediately after birth, and then at age 6 months and 1 year, and Der p 1 levels were determined by mAb-based ELISA. Results: Recovered Der p 1 from maternal mattress was reduced by 97.25% (95% confidence interval [CI] 95.25%-98.41%) during the second and third trimesters of pregnancy, with the effect persisting for 6 months (98% reduction, 95% CI 97.25%-99.1%) and 12 months (97.6% reduction, 95% CI 95.7%-98.6%) after the birth (active vs control, P < .000001). Total Der p 1 from bedroom floor in the active group was reduced by 53.7% (95% CI 25.7%-71.2%) in samples collected within 4 weeks of the child's birth, with the percentage reduction being 62.8% (95%